"Who Is A Jew?" Reflections on History, Religion, and Culture - Greenspoon, Leonard (Purdue University Press, 2014)
Jewish identity is a perennial concern, as Jews seek to define the major features and status of those who "belong," while at the same time draw distinctions between individuals and groups on the "inside" and those on the "outside." From a variety of perspectives, scholarly as well as confessional, there is intense interest among non-Jewish and Jewish commentators alike in the basic question, "Who is a Jew?" This collection of articles draws diverse historical, cultural, and religious insights from scholars who represent a wide range of academic and theological disciplines. Some of the authors directly address the issue of Jewish identity as it is being played out today in Israel and Diaspora communities. Others look to earlier time periods or societies as invaluable resources for enhanced and deepened analysis of contemporary matters. All authors in this collection make a concerted effort to present their evidence and their conclusions in a way that is accessible to the general public and valid for other scholars. The result is a richly textured approach to a topic that seems always relevant. If, as is the case, no single answer appeals to all of the authors, this is as it should be. We all gain from the application of a number of approaches and perspectives, which enrich our appreciation of the people whose lives are affected, for better or worse, by real-life discussions of this issue and the resultant actions toward exclusivity or inclusivity.